2017
DOI: 10.3389/fmicb.2017.00067
|View full text |Cite
|
Sign up to set email alerts
|

Metatranscriptomics Reveals the Active Bacterial and Eukaryotic Fibrolytic Communities in the Rumen of Dairy Cow Fed a Mixed Diet

Abstract: Ruminants have a unique ability to derive energy from the degradation of plant polysaccharides through the activity of the rumen microbiota. Although this process is well studied in vitro, knowledge gaps remain regarding the relative contribution of the microbiota members and enzymes in vivo. The present study used RNA-sequencing to reveal both the expression of genes encoding carbohydrate-active enzymes (CAZymes) by the rumen microbiota of a lactating dairy cow and the microorganisms forming the fiber-degradi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
111
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(119 citation statements)
references
References 75 publications
(115 reference statements)
8
111
0
Order By: Relevance
“…Not unexpectedly, the well-studied fibrolytic bacteria Fibrobacter succinogenes represented the bacterial species with the highest number of detected proteins (switchgrass: 349; rumen fluid: 210), followed by two strains of Prevotella ruminicola (ranging from 173 to 213 proteins, of which the majority of the detection proteins were homologues of the two strains) and P. brevis (switchgrass: 129; rumen fluid: 168), highlighting their overall importance in the carbohydrate metabolisms in the rumen. This is consistent with previous studies involving functional analysis of the rumen microbiome, demonstrating that a majority of the plant cell wall polysaccharide degradation is carried out by species related to Fibrobacter, Ruminococcus and Prevotella 24,25,36 . Although our metaproteome data suggested that these aforementioned characterized prokaryotes were amongst the most active (i.e.…”
Section: Figuresupporting
confidence: 93%
See 2 more Smart Citations
“…Not unexpectedly, the well-studied fibrolytic bacteria Fibrobacter succinogenes represented the bacterial species with the highest number of detected proteins (switchgrass: 349; rumen fluid: 210), followed by two strains of Prevotella ruminicola (ranging from 173 to 213 proteins, of which the majority of the detection proteins were homologues of the two strains) and P. brevis (switchgrass: 129; rumen fluid: 168), highlighting their overall importance in the carbohydrate metabolisms in the rumen. This is consistent with previous studies involving functional analysis of the rumen microbiome, demonstrating that a majority of the plant cell wall polysaccharide degradation is carried out by species related to Fibrobacter, Ruminococcus and Prevotella 24,25,36 . Although our metaproteome data suggested that these aforementioned characterized prokaryotes were amongst the most active (i.e.…”
Section: Figuresupporting
confidence: 93%
“…and the two Piromyces species, had the highest LFQlevel of all cellulases. While GH48 have been absent or only detected at very low levels in previous rumen metagenomes 31,38 , members of this GH family have been observed in rumen metatranscriptomes from mixed rumen populations, reportingly expressed by Ruminococcus and rumen fungi 24,25,39 . It is also worth noting that while members of the GH48 family were the most abundant CAZymes affiliated to protein sequences of Orpinomyces sp.…”
Section: Metaproteome-generated Cazyme Profile Indicates Compartmentamentioning
confidence: 99%
See 1 more Smart Citation
“…Shotgun metagenomic analysis randomly sequencies the DNAs present in environmental samples using a next-generation sequencer, which provides an effective method to determine microbial composition and general function from uncultivated microorganisms [33]. Several studies have conducted metagenomic analysis in cow rumen and revealed the several microbes that are involved in the decomposition of the plant cell wall decomposition [3, 5]. However, the pretreatment process is an unbuffered closed system that treats a single substrate.…”
Section: Introductionmentioning
confidence: 99%
“…Transcripts with E values < 1e-6 were kept. The E-value cutoff was selected based on previous studies Quandt et al, 2015;Comtet-Marre et al, 2017;Meiser et al, 2017;Gonzalez et al, 2018) and after manual examination of a subset of sequences and their BLASTX results. To gain more taxonomic information and to confirm that the selected transcripts really belong to fungi, transcripts were first translated into proteins with Transdecoder (Haas et al, 2013) and an additional round of BLASTP against the NCBI Non-Redundant (NR) protein database was performed, saving the top five hits.…”
Section: Fungal Nutrient Transporters (Amino Acids [Organic Nitrogen]mentioning
confidence: 99%